Forearc structure and morphology along the Sumatra‐Andaman subduction zone. Issue 2 (25th February 2014) - McNeill, Lisa C.; Henstock, Timothy J.
Abstract The Sunda subduction margin, the location of recent magnitude 8–9 megathrust earthquakes, is characterized by major changes in prism and forearc morphology and structure along its 5000 km length. On the Sumatra‐Andaman section, measurements of prism width and surface slope (α) indicate along‐strike segments, inclu1ding abrupt changes, of prism morphology: (1) a narrow and steep prism between Burma and the Andamans; (2) broad with an averaged gentle slope in the Andamans, Nicobars, and North Sumatra; (3) steep and narrow in Central Sumatra; and (4) wider and less steep offshore South Sumatra, decreasing in width to West Java. Prism width varies from ~90 to 180 km and average surface slope from ~1 to 3° with a strong inverse correlation between width and slope, also observed globally. The prism deviates from typical taper geometry in parts of the margin, notably offshore North Sumatra where it is characterized by a steep toe and broad plateau. Along‐strike changes in morphology are strongly linked to input sediment thickness. Sections of the prism toe represent key global examples of unusual landward vergent thrusting. These sections correspond to a thick sediment input and to a wide prism with shallow surface slope. A low basal shear stress or backstop mechanism may drive this style of faulting. Prism morphology and structure appear to be driven predominantly by input sediment thickness linked to oceanic basement topography, with sediment properties, plate smoothness, and orthogonal subduction rate and obliquity also contributing, and no clear role of plate age or dip.